Approaches to profit and cost management system of households within national economy - Lipych, Liubov G.; Ivashko, Olena A.; Mostenets, Sergiy V. (My University, 2016)
The paper presents the contemporary approaches to interpretation of profit and cost management system of households. The method of efficiency estimation for households profit and cost management is offered. An optimization model of profit and cost management system has been developed to increase their profits and enable further investment. The need for state support in developing the households of the investment type is grounded, viewed as an impetus that will enhance the investment capacity of population
Keywords: household; profit and cost management; investment potential of households